Complications following breast cancer therapy in the adult spina bifida population: A case report - Hoy, Nathan Y; Metcalfe, Peter (Canadian Urological Association Journal, 2013)
Survival to adulthood in spina bifida has greatly increased with the advent of modern therapies. With this prolonging of life expectancy, patients are exposed to the risk of adult onset malignancies and the complications of subsequent treatment. We present the case of a 66-year-old woman born with a terminal lipomyelomeningocele, presenting with new fecal incontinence and a desire to undivert her ileal conduit. The deterioration was attributed to chemotherapy for breast cancer. We highlight the urologic challenges of breast cancer management in the neurogenic bowel population, as well as the utility of an adult spina bifida clinic. To the best of our knowledge, this is the first case report of a spina bifida patient presenting with fecal and urinary complications from breast cancer chemotherapy.